Atomic oxygen erosion behaviors of PBO fibers and their composite: Microstructure, surface chemistry and physical properties. (November 2016) - Chen, Lei; Wang, Caifeng; Wu, Zijian; Wu, Guangshun; Huang, Yudong
Abstract: Poly( p -phenylene benzobisoxazole) (PBO) fibers are ideal candidates for cables in tether application and reinforcements in advanced composites. Upon exposure to atomic oxygen (AO) in low earth orbit (LEO), PBO fibers are severely eroded. In this study, the AO erosion behaviors of PBO fibers and their composite were investigated in simulated AO environment, based on the evaluation of microstructure, surface chemistry, thermal stability and mechanical properties. Surface morphologies and crystalline structure confirmed that PBO fibers were significantly eroded after AO irradiation. X-ray photoelectron spectroscopy (XPS) showed that the relative content of CC decreases with the increase of AO irradiation time, suggesting a chain scission of PBO fibers. After 8 h AO exposure, the tensile strength of PBO fibers was decreased by 31.6%, and the onset decomposition temperature was reduced by 30.8 °C. Monofilament pull-out tests showed that the interfacial shear strength (IFSS) of PBO/epoxy composite was as low as 61.3% that of pristine composite due to the interface damage caused by AO penetration.